Cadmium level in pregnancy, influence on neonatal birth weight and possible amelioration by some essential trace elements (2013)
Cadmium (Cd) is currently of great concern in rapidly industrializing countries‑India, China. Their products consumed especially due to increase demand in many developing countries like Nigeria can result in adverse effects. Cd is a ubiquitous environmental pollutant and toxicant and humans are continually exposed to the toxic effects of Cd primarily through food as well as from environmental pollution through industrial activities. Maternal exposure to Cd has been associated with the delivery of low‑birth weight babies and an increase incidence of spontaneous abortion. Cd a toxic metal can displace zinc (Zn) an essential element necessary for normal fetal development and growth. With this consideration, 160 subjects comprising of 125 pregnant and 35 non‑pregnant subjects as controls were recruited for this study. The pregnant subjects were classified according to the three trimesters of pregnancy as followed; 35, 35, and 55 from the first to the third trimesters respectively. The third trimester subjects were followed‑up until after delivery where neonatal parameters (birth weight, head circumference, and length) of babies were measured. 32 (58%) of the women delivered babies with normal birth weight, 19 women (35%) delivered babies with low‑birth weight while four women (7%) delivered babies with high‑ birth weight. Subject who delivered low‑birth weight babies had significantly higher Cd concentration and lower Zn concentration and body mass index when compared with those with normal weight babies. These results suggest that Cd indeed has some toxic effects on neonatal birth weight.